Participatory community nutrition education: Training manual for community health workers - Induli, Irene; Odour, Francis; Boedecker, Julia; Akutau, Nelson Lobolia; Mwaura, Joel Kiarie; Termote, Céline; Jordan, Irmgard (2022)
This manual has been developed based on participatory workshops and subsequent agri-nutrition training courses in Vihiga County, Western Kenya by the Alliance of Bioversity International and CIAT. This manual was further evaluated in Turkana and Busia Counties in Kenya, with the intention to develop agricultural interventions to improve nutrition. The learning objectives for the training are focused on: (1) basic principles of nutrition; (2) a life-cycle approach to nutrition; (3) home gardening; (4) use of underutilized crops to diversify diets; and (5) a practical cooking demonstration session.